Evaluating the association between pedagogical approaches and mathematics performance of grade VI learners in Naval district, Philippines - Inot, Charmaine (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study investigates the link between instructional strategies implemented by teachers and the mathematics achievement levels of Grade VI students in Naval District, Philippines. Given the persistently low mathematics scores failing to reach district standards, understanding potential factors influencing student performance becomes crucial. Method: A descriptive-correlational research approach was employed, involving Grade VI students, teachers, and school administrators across selected schools in Naval District. The study utilized standardized mathematics achievement assessments aligned with the Philippines' Grade VI curriculum to measure student proficiency. Teachers’ instructional practices were evaluated using validated questionnaires derived from the Philippine Professional Standards for Teachers. The collected data were statistically analyzed using frequency distribution, means, standard deviations, Pearson correlation coefficient, and Chi-square tests. Findings: The study found that the majority of students demonstrated an average level of mathematical proficiency. Teachers reported consistently high usage of various instructional practices including teaching methodologies, learning resources, and assessment techniques. Importantly, significant correlations were identified between teachers' duration of service, their subject specialization, and students' mathematical competencies. Conversely, instructional strategies alone showed no direct significant relationship with students' performance. Significance: The outcomes of this research offer significant insights for educational leaders and policymakers, highlighting the importance of teacher experience, specialization, and continuous professional growth. By pinpointing these critical factors, the study recommends targeted professional training and tailored intervention programs to enhance mathematical performance among primary school learners, contributing to overall improvements in educational quality.